(untitled) (Journal of Nobel Medical College, 2023)
Background: The social media use and its impact on employee self-confidence in the workplace have garnered attention and concern. However, limited studies exist in the Nepali context. Therefore, researchers aim to examine the influence of social media use on Employee Self-Confidence and explore the moderating role of age in the relationship betweenSocial media use and employee self-confidence. Materials and Methods: Utilizing a quantitative cross-sectional design and convenience sampling, data were collected from July to Aug, 2022, via Google Forms for selected health institutes in Kathmandu Valley. The sample size was 149. Ethical clearance was obtained from Yeti Health Science Academy, IRC, recognized by the Nepali Health Research Council. Modified 11-point items, using a 5-point Likert scale (1 to 5) for social media use and employee self-confidence, were validated through pilot tests, Cronbach’s alpha, factor analysis, and content validity. The independent variables of social media use and employee self-confidence exhibited robust performance, providing valuable insights for the study. Results: Researchers conducted descriptive, regression, and moderation analyses to examine the frequency, influence, and moderating role of age in this study. Facebook emerged as the preferred social media platform. The analysis revealed that social media use has a significantly positive influence on employee self-confidence (Beta = 0.588, p < 0.001). Age significantly moderates the relationship between social media use and employee self-confidence, with beta values indicating a negative relationship. Conclusion: Social media use is gaining popularity, even in health institutes. Effectively utilized, it contributes significantly to the workplace, as evidenced in this study. Age also showed a moderating role, suggesting health care leadership should initiate interventions to foster social media use among employees for increased confidence, and performance.